The Effect of Transformational Leadership Style, Flexible Workplace, Work Motivation, and Organizational Culture on Employee Performance in Generator Set Repair Services in DKI Jakarta - Naldo, Daffa Aldin (Jurnal Indonesia Sosial Sains, 2025)
This study aims to analyze the influence of Transformational Leadership Style (X1), Flexible Working Place (X2), Work Motivation (X3), and Organizational Culture (X4) partially and simultaneously on Employee Performance (Y) at PT. Messawa Sole Ambassador. This study uses a quantitative approach with the Descriptive Analysis method. The population in this study is all employees of PT. Messawa Tunggal Ambassador, with a sample of 200 people. respondents determined through the Convenience Sampling technique. Primary data collection was carried out by distributing questionnaires measured using the Likert scale. The data analysis technique used was multiple linear regression analysis with the help of Smart PLS."